Hubungan Kondisi Lingkungan dengan Kasus Filariasis di Masyarakat (Analisis Lanjut Hasil Riskesdas 2007) - Santoso Santoso (Loka Litbang Kesehatan Pangandaran, 2011)
Abstracts. Filariasis (elephantiasis disease) in Indonesia is still a health problems, there arestill areas with the patient chronic and acute. A total of 1553 villages in 647 health centersscattered in 231 districts in 26 provinces as the location of the endemic, with a number ofchronic cases of 6233 people. Elimination program disease elephantiasis has beenundertaken by the government, but until today there are still many areas with the number ofmicrofilariae (Mf rate) is still high (> 1%). One of the government's efforts in this regardLitbangkes RI in collecting basic data, including data filariasis is with the activities of theBasic Health Research (Riskesdas) conducted simultaneously across Indonesia. Based onthe results of data collection Riskesdas then further analysis is to look at the environmentalconditions and demographic status associated with the incidence of filariasis. Based on theresults of analysis show that there were a statistically significant relationship between thetype of waste water reservoirs; types of sewage systems and types of livestock kept, theclassification of villages with the incidence of filariasis.